Concept of 'Meaning of Words and Terms' in Elementary School learning: A review of literature - Elihami Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Many words are associated with more than one meaning. Words are sometimes "ambiguous", applying to unrelated meanings, but most of the words that occur frequently are "polysemy" because they apply to several related meanings. In a pre-registration design that includes 2 tasks, we test the ability of adults and children aged 4.5 to 7 years to learn 4 new polysemy words or 4 new ambiguous words especially in Indonesian subjects in primary school learning in learning in elementary school. Both children and adults demonstrated the superiority of polysemic learning over ambiguity on each task after exposure, showing better learning of new words with multiple related meanings than new words with unrelated meanings in primary school learning. We concluded that participants were adept at learning polysemy words that varied across multiple dimensions. The current results are consistent with the idea that the ambiguous meanings of a word compete, but that polysemous meanings reinforce each other in primary school learning.